2010
DOI: 10.1111/j.1742-7843.2010.00648.x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel COX‐2 Inhibitor Pyrazole Derivative Proven Effective as an Anti‐Inflammatory and Analgesic Drug

Abstract: The introduction of new COX-2 inhibitors with high efficacy and enhanced safety profile would be a great achievement in the development of anti-inflammatory drugs. This study was designed to screen and assess the anti-inflammatory and analgesic activities as well as some of the expected side effects of some pyrazole derivatives, newly synthesized as potential COX-2 inhibitors at the Faculty of Pharmacy, Alexandria University and compared to indomethacin and celecoxib. Twelve compounds were screened for their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…Therefore, decreases in COX-2 immunoreactivities have been used to predict the favourable effects of test materials on inflammation [32, 33]. In addition, increases in iNOS activities related to proinflammatory agents, such as endotoxin, IL-1β, TNF-α and interferon-γ, can be induced by shock and also occur following inflammatory responses in the body [34].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, decreases in COX-2 immunoreactivities have been used to predict the favourable effects of test materials on inflammation [32, 33]. In addition, increases in iNOS activities related to proinflammatory agents, such as endotoxin, IL-1β, TNF-α and interferon-γ, can be induced by shock and also occur following inflammatory responses in the body [34].…”
Section: Discussionmentioning
confidence: 99%
“…Chemical mediators invoke synthesis of PGE 2 in monocytes, neutrophils, and endothelial cells at sites of inflammation; therefore, PGE 2 has been reported to a play a critical role in the inflammatory response [29]. Accordingly, decreases in the level of PGE 2 have been considered valuable in prediction of the favorable effects of test materials on inflammation [30, 31]. Results of the PGE 2 assay and Western blotting analysis of COX-2 revealed that treatment with PWS resulted in significantly inhibited induction of PGE 2 and COX-2 protein by LPS (Figures 2(a) and 3(a)), suggesting that PWS could have a therapeutic effect in treatment of pathogenic heat and pain.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, researchers are seeking new molecules with comparable efficacy to known NSAIDs but with better safety profile. Mohy EL-Din et al (2010) found a new compound containing 4-(3-(4-methylphenyl)-4-cyano-1H-pyrazol-1-yl) benzenesulfonamide with good anti-inflammatory effect, no ulcerogenic effect, and minimal effect on the kidneys. Thore et al (2012) synthesized a series of novel ethyl-5-amino-3-methylthio-1H-pyrazole-4-carboxylates.…”
Section: Introductionmentioning
confidence: 99%